Penggunaan game edukasi digital pada pembelajaran ilmu pengetahuan alam: Persepsi dan pengetahuan siswa - Aditia, Anggita; Hamka, Defrizal (Jurnal Pendidik Indonesia, 2021)
This research aims to assess students' level of knowledge through their perception of using digital educational games in Science (IPA) learning. The type of research conducted is descriptive quantitative, and for this study, questionnaires and interviews were used as instruments to collect data. The data analysis technique applied is the Miles and Huberman Interactive Model. This research was conducted at one of the junior high schools in Pekanbaru, with 30 student subjects. The results of the study show that the majority of students know educational games. Most students agree that using educational games as a learning medium helps them understand the concept of the solar system in the Science subject. This finding provides a positive outlook on the potential of digital educational games as effective learning aids. This research offers new insights into students' perception of using educational games in Science learning.